Anti-Inflamasi Tanaman Kedondong (Spondias Dulcis G. Forst.): Review - Raudhah Hayatillah; Widie Kemala Hapsari (Universitas Muslim Buton, 2023)
Technological developments are currently growing, this can be seen from the increasing lifestyle of people, one of which is the increased consumption of fast food or junk food, it is known that fast food has low nutritional content and high calories, so it can trigger inflammation in the body accompanied by the emergence of disease. which is harmful to the body if consumed for a long time. To minimize the occurrence of disease, in recent years scientists have been intensively conducting research on the discovery of new drugs derived from plants, one of the plants that has the potential as an anti-inflammatory is the kedondong plant. The purpose of writing this article is to find out the potential of the kedondong plant as an antioxidant and anti-inflammatory. Based on testing with several extraction methods and compound test methods, bioactive compounds were found, the compounds contained were phenolics, tannins, saponins and flavonoids which are a group of antioxidant compounds. These compounds were found in leaves, stems, fruits and roots, every part of the kedondong plant has bioactive compounds, through tests carried out. The bioactive compounds in kedondong are known to reduce the expression of iNOS, TLR4, Th1, interleukin (IL) and cytokines genes, these genes are expressed genes in the process of inflammation. So that the antioxidant content in the kedondong plant has the potential as an anti-inflammatory by inhibiting the genes that are expressed in the process of inflammation. The content of bioactive compounds contained is also influenced by the solvent in the extraction process carried out.